Treatment of superficial second-degree burns with a nanofiber tissue matrix: A case report. Issue 4 (October 2022) - Rodriguez, John Clayton; Chen, Andy H.; Carney, David E.
Highlights: Various treatment modalities exist for superficial partial thickness burns. Novel, synthetic nanofiber matrices offer many advantages. Widely available, easy to use, aesthetically-pleasing. Abstract: Burn wound management has continued to evolve with advances in the understanding of wound healing. Treatment of partial-thickness burns consists of a wide variety of dressings and biosynthetic skin substitutes all with the goal of providing wound coverage while promoting healing. In this paper, we describe the successful treatment of a 6% total body surface area superficial second-degree thermal burn with the application of a novel fully synthetic nanofiber matrix.